Direct and spillover effects of land rights formalization in Africa: A case study of the Second-Level Land Certification (SLLC) in Ethiopia - Ghebru, Hosaena; Girmachew, Fikirte (International Food Policy Research Institute, 2020)
The study investigates the overall impacts of a second level land certification (SLLC) program in Ethiopia using a three-wave panel data set 3092 households collected in 2013, 2015 and 2018. The fact that the first-round survey was administered just before the SLLC program was launched in 2013/14 provides a unique opportunity to evaluate the impacts of the program using data before and after the program was launched. After controlling for potential selection bias, overall results show no evidence of diminishing returns to the first level land certification (FLLC) as SLLC program participation shows no statistically significant effect on household perceived tenure security. A more gender disaggregated investigation indicates a relatively favorable outcome on married women’s perceived tenure security compared to their male counterparts. Empirical results also reveal a market stimulant effect of the SLLC program on land rental market participation with a more direct effect on beneficiary households’ likelihood of renting out land (becoming a landlord) and a spillover benefit to non-beneficiary households’ likelihood of renting-in land (becoming a tenant). Finally, our analysis shows a negative and statistically significant impact on access to and/or control over land by women and youth. Such evidence demands the need for future designing and implementation of similar programs to integrate a more gender and age sensitive parameters so that program outcomes remain desirable/favorable for such vulnerable groups.